(5,6-Dimethyl-1,10-phenanthroline)(2-{[2-(diphenylphosphanyl)benzylidene]amino}ethan-1-amine)platinum(II) dinitrate methanol disolvate - Ashley Jurisinec; Yingjie Zhang; Janice R. Aldrich-Wright (Acta Crystallographica Section E: Crystallographic Communications)
The title compound, [Pt(C14H12N2)(C21H21N2P)](NO3)2·2CH3OH, is a platinum(II) complex, which crystallizes in a monoclinic (P21/c) space group. The complex exhibits a distorted square-planar geometry, which includes a monodentate 5,6-dimethyl-1,10-phenanthroline ligand and a tridentate 2-{[2-(diphenylphosphanyl)benzylidene]amino}ethan-1-amine ligand. The structure reveals both intra- and intermolecular π-stacking interactions between the phenanthroline and phosphine rings. Hydrogen bonding is observed between the complex ion, nitrate counter-ions and solvent molecules.